Implementation of Inclusive Education Based on Child Friendly Learning in Early Childhood Education - Ainul Hasanah; Barratun Naqiyah; Itaul Hasanah; Imroatus Sholeha; Khoiratul Ummah (Lembaga Bale Literasi, 2025)
Inclusive education for early childhood is a strategic effort to guarantee the right of every child to obtain fair, quality, and non-discriminatory educational services, including for children with special needs. This study aims to describe the implementation of inclusive education in Early Childhood Education (PAUD) units, particularly in the planning, implementation, and evaluation of child-friendly and non-discriminatory learning. This study uses a qualitative approach with a case study method. The research subjects included the head of the PAUD unit, educators, and parents of students, while data collection techniques were carried out through observation, in-depth interviews, and documentation studies. The results of the study indicate that the implementation of inclusive education in PAUD has been carried out through the application of differentiated learning, curriculum adjustments, the use of flexible play strategies, educator competence, collaboration with parents and experts, and the availability of complete and inclusive facilities and infrastructure. This study concludes that the success of inclusive education in early childhood is largely determined by the readiness of the institution to accommodate the diverse needs of students, educator competence, adequate facilities and infrastructure, and synergy with parents and related parties/experts.